Positioning higher education institutions : from here to there - Pritchard, Rosalind M. O. (Rotterdam, The Netherlands ; Boston : Sense Publishers, [2016], 2017)
Higher education is of growing public and political importance for society and the economy. Globalisation is transforming it from a local and national concern into one of international significance. In order to fulfil societal, governmental and business sector needs, many universities are aiming to (re-)position themselves. The book initially considers their "compass". They aspire to transformational planning, mission and strategy in which social justice is important, people are not treated as mere means to an end, and traditional moral positions are respected. This transformational urge is sometimes vitiated by blunt demands of new public management that overlook universities? potential for serving the public good. The volume then addresses universities? success in meeting their targets. Often the challenge in evaluation is the need to reconcile tensions, for example between structure and pastoral care of students; institutional competition and collaboration; roles of academics and administrators; performance-based funding versus increased differentiation. Measurement is supposed to provide discipline, align institutional and state policy, and provide a vital impetus for change. Yet many of these measurement instruments are not fully fit for purpose. They do not take sufficient account of institutional missions, either of "old" or of specialist universities; and sophisticated measurement of the student experience requires massive resources. Change and positioning have become increasingly key elements of a complex but heterogeneous sector requiring new services and upgraded instruments.